2018
DOI: 10.1111/evj.13011
|View full text |Cite
|
Sign up to set email alerts
|

Clodronate improves lameness in horses without changing bone turnover markers

Abstract: A single dose of clodronate appears to reduce lameness without producing detectable effects on bone turnover markers. Due to the long half-life of a bisphosphonate drug, the effect of multiple doses on bone remodeling and lameness should be investigated. This article is protected by copyright. All rights reserved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
16
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 48 publications
(72 reference statements)
5
16
1
Order By: Relevance
“…Subjective lameness and subjective joint effusion scores were reported as ordinal variables but analysed using a repeated measures two‐way ANOVA to take into consideration related, non‐independent groups, sampled over multiple time points. Although this analysis is consistent with multiple previous publications, a non‐parametric analysis could have been performed on these data. Due to the potential controversial nature of this analysis, both subjective lameness and subjective effusion were also assessed by continuous variables (vector sum and joint circumference), and the authors confirmed that analysis of the groups at 6, 12 and 24 h using a nonparametric statistical test (Wilcoxon matched pairs signed rank test) was also unable to identify a difference between groups (data not shown).…”
Section: Discussionsupporting
confidence: 86%
“…Subjective lameness and subjective joint effusion scores were reported as ordinal variables but analysed using a repeated measures two‐way ANOVA to take into consideration related, non‐independent groups, sampled over multiple time points. Although this analysis is consistent with multiple previous publications, a non‐parametric analysis could have been performed on these data. Due to the potential controversial nature of this analysis, both subjective lameness and subjective effusion were also assessed by continuous variables (vector sum and joint circumference), and the authors confirmed that analysis of the groups at 6, 12 and 24 h using a nonparametric statistical test (Wilcoxon matched pairs signed rank test) was also unable to identify a difference between groups (data not shown).…”
Section: Discussionsupporting
confidence: 86%
“…In this light, we recently reported the results of a small equine study in which the bone turnover markers C-terminal collagen-I telopeptide (CTX-I) and osteocalcin were measured following a single clodronate injection (IM) (1.4 mg/kg). Weekly blood draw and analysis revealed no significant effects on bone turnover markers, but did appear to reduce lameness [22]. These findings are consistent with the work of others [27] that showed tiludronate and clodronate ( Fig.…”
Section: Introductionsupporting
confidence: 90%
“…Given the rampant BP use in the equine industry, there are only a few reports demonstrating a positive effect of either BP approved for use in horses with navicular syndrome [15,16,27] and none report bone-related complications. However there is a report that documented lack of change in bone resorption following tiludronate (1 mg/kg IV) or clodronate (1.8 mg/kg IM) treatment [27] as well as a lack of any significant change in serum markers of bone turnover following clodronate (1.4 mg/ kg IM) treatment [22]. In contrast, the majority of human studies report both beneficial and not so beneficial effects of BP therapy in the treatment of postmenopausal osteoporosis and bone metastasis [9,10,12,[29][30][31][32].…”
Section: That Is Important Information But What Are the Down Sides?mentioning
confidence: 99%
See 1 more Smart Citation
“…As lameness evaluation is a very subjective process and taken together with the fact both studies are "multicentric", the accuracy of the outcome evaluation is questionable. Unlike more recent studies on the topic (Mitchell, A. et al 2019 and Whitfield, C.T. et al 2016), no inertial sensor system nor ground-mounted stationary force plate system was employed.…”
Section: Appraisal Application and Reflectionmentioning
confidence: 99%